Comparative Study of a Three Phase Cascaded H-Bridge Multilevel Inverter for Harmonic Reduction - Rosli Omar; Mohammed Rasheed; Marizan Sulaiman; M. R Tamijis (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The aim of this research project is to analyze and design of energy storages in electrical distribution system. In this paper presents a comparative study between sinusoidal pulse width modulation (SPWM) and space vector pulse width modulation (SVPWM) technique, based on generate signal five level of cascaded H-bridge for reduction harmonics in the multilevel inverter output. A multilevel inverter is a preferred choice for most medium-voltage and high-power applications, as well as cascaded H-bridge (CHB) five-level inverters due to its advantages such as low cost, light weight and compact size. It is suitable particularly for use in a cascaded H-bridge multilevel inverter due to reduced total harmonic distortion (THD). Harmonic content in three phase multilevel inverter can be investigated by generating (SPWM) and (SVPWM) algorithm signal based on a five-level (CHB). The proposed system is designed using MATLAB/SIMULINK consists of cascaded H-bridge (CHB) multilevel inverter. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7949